2022
DOI: 10.33506/sl.v11i1.1505
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Good Corporate Governance (Empirical Studies on Companies Listed on The IDX)

Abstract: The purpose of this study is the role of ownership concentration, firm size, and leverage in influencing good corporate governance. This research design is quantitative. The population used is 45 companies indexed LQ45 on the Indonesia Stock Exchange and with the Purposive Sampling method, obtained 17 companies with 3 years of observation, so the number of samples in this study is 51. The results show that the concentration of ownership, company size, and leverage have a significant effect. The test results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
0
0
1
Order By: Relevance
“…The results of this research are also supported by (Abdi et al (2022), who found that the governance dimension in ESG significantly positively influences company value. This is because of the real benefits that underlie good corporate governance policies, such as implementing responsible leadership and independent supervision to ensure maximum shareholder benefits and implementing sustainable reporting strategies.…”
Section: The Influence Of Corporate Social Responsibility (Csr) On Co...supporting
confidence: 75%
“…The results of this research are also supported by (Abdi et al (2022), who found that the governance dimension in ESG significantly positively influences company value. This is because of the real benefits that underlie good corporate governance policies, such as implementing responsible leadership and independent supervision to ensure maximum shareholder benefits and implementing sustainable reporting strategies.…”
Section: The Influence Of Corporate Social Responsibility (Csr) On Co...supporting
confidence: 75%
“…Hasil penelitian kesempatan investasi tidak berpengaruh terhadap GCG didukung temuan (Chandra & Yusbardini, 2020;Ramadhan & Laksito, 2019;Wahyudin & Solikhah, 2017). Namun tidak didukung penelitian terdahulu yang menemukan adanya pengaruh kesempatan investasi terhadap GCG (Adha, 2022;Praditha et al, 2022;Rahayuningsih, 2013). Karakteristik tidak berpengaruh terhadap GCG.…”
Section: Pembahasanunclassified